Hemodialysis in cadaveric renal transplantation with acute renal failure - Kurita, Takashi; Koghi, Yukito; Imada, Akio (Journal of Japanese Society for Dialysis Therapy, 1990)
Dialysis therapy was administered in the treatment of acute renal failure (ARE) occurring after cadaveric renal transplantation, and the changes in various laboratory findings during dialysis were analyzed. The subjects of this study were 32 patients who underwent cadaveric renal transplantation during the period from 1980 through 1988. They consisted of 18 males and 14 females, and their ages ranged from 14 years to 56 years (mean±SD: 33.8±8.4 years). These patients were classified into 3 groups consisting of 1. those who received no dialysis therapy (non-dialysis group), 2. those who received dialysis therapy and were able to withdraw from dialysis therapy due to the recovery of renal function (withdrawal group) and 3. those who could not withdraw from dialysis therapy (non-withdrawal group). For each group, the correlation between the ischemic time during transplantation and the results of laboratory tests performed during the 6-day period after transplantation was studied. Also, the influence of ischemic time on laboratory test values and the duration of dialysis was studied. For the withdrawal group, the levels of various laboratory test parameters at the time of withdrawal were also studied. Of the 32 patients, 23 (71.9%) required dialysis therapy: Hemodialysis in 19 and peritoneal dialysis in 4. Of the 23 patients, 18 (78.3%) were able to withdraw from dialysis, and the duration of dialysis was 2-31 days (mean±SD: 11.8±8.7 days). A positive correlation at r=0.53 (p<0.005) was detected between the duration of dialysis and the warm ischemic time (WIT) in the withdrawal group. During the period of anuria after cadaveric renal transplantation, non-anticoagulant hemodialysis was performed using a blood tubing set which was designed to prevent activation of the blood coagulation system. Because of this system, no bleeding occurred during hemodialysis. Hemodialysis after cadaveric renal transplantation was necessary when no urination was seen within 2 days after the operation, and the non-anticoagulant dialysis method proved effective. It was concluded that withdrawal from dialysis therapy becomes possible when the daily urinary volume exceeds 800-1, 000ml.